Moving from production to services: A built environment cluster framework - Carassus, Jean; Andersson, Niclas; Kaklauskas, Artūras; Manseau, André; Ruddock, Les; Valence, Gerard de (International Journal of Strategic Property Management, 2010)
The construction industry is no longer focused on providing a single product – i.e. a building or a physical infrastructure, but a variety of services and improvement to the human environment. Major trends such as Performance‐based Building as well as Sustainable Built Environment are calling for major changes. These changes mean additional roles for the industry as well as the need for new indicators to measure its performance and its economic impact. This paper proposes a new approach based on the development of a framework for the analysis of the entire construction and property sector – the “built environment cluster”. It extends the analysis of an international study based on nine countries – Australia, Canada, Denmark, France, Germany, Lithuania, Portugal, Sweden, and the United Kingdom. The need for improving statistical data is stressed particularly in the context of enlarging the scope of the industry. This new approach provides an excellent starting point for developing new performance indicators that will take into account the changing nature of the industry, for an integrative perspective providing a basis for strategic management, for studying sustainable development in construction and for understanding innovation processes and changes. A comprehensive perspective of the industry performance is crucial for policy initiatives as well as for strategic analysis of firms.First Published Online: 18 Oct 2010